Herbicide exposure and tumor mortality. An updated epidemiologic investigation on Swedish railroad workers. - Axelson, Olav; Sundell, Lennart; Andersson, Kjell; Edling, Chister; Hogstedt, Christer; Kling, Hans (Scandinavian Journal of Work, Environment & Health, 1980)
An earlier cohort study of Swedish railroad workers indicated a possible relationship between exposure to herbicides and an increased overall tumor morbidity and mortality. The cohort of 348 individuals has now been followed through October 1978. In this updated analysis of the causes of death among railroad workers, the observed number of tumor deaths was higher than expected, especially among individuals exposed in the earlier years of the study to both amitrol and phenoxy acids. However, the excess tumor mortality among persons exposed to amitrol became more moderate, and the earlier, slightly increased tumor mortality among people exposed to phenoxy acids more pronounced. No specific type of tumor predominated although there were three stomach cancers and three lung cancers. The result of the previous analysis of deaths among these railroad workers has been confirmed as to an excess of tumors, but the aspects of causal relationships to specific agents remain rather unclear, especially since workers exposed to a combination of amitrol and phenoxy acids seem to be the most seriously affected. However, the result, being in agreement with animal data and other epidemiologic studies, suggests a need for the careful handling of amitrol and phenoxy acids as increasingly suspicious carcinogens.
Keywords: 2; 4-dichlorophenoxy acetic acid; 2; 4; 5-trichlorophenoxy acetic acid; amitrol; cancer; diurone; epidemiologic investigation; epidemiology; exposure; herbicide; herbicide exposure; monurone; mortality; phenoxy acid; railroad worker; Sweden; tumor; tumor mortality; worker